University Education Fees, Economic Rents and Distributive Justice. - Lamont, Julian (Journal of Applied Philosophy, 2014)
In this article I defend the claim that subsidies for university education should be substantially reduced. The normative justification for this conclusion derives from a theory of distributive justice called the Compensation Theory of Income Justice, which is most easily understood as a normative version of the positive economic theory of compensating differentials. Relying on the distinction between incentives and economic rents, and after considering two 'received opinions' about why large income differentials exist in modern societies, I note that substantial portions of above-average incomes are likely to be artificial monopoly rents, rather than incentives or natural monopoly rents. Under the Compensation Theory of Income Justice the earning of artificial monopoly rents is not justified. Since subsidisation of university education fees increases lifetime artificial rents, the theory would recommend such subsidies be substantially reduced. I defend this conclusion against objections, the most notable of which is the view that university subsidies help to improve equality of opportunity to university education. I explain how it is possible to maintain the laudable aim of providing equality of opportunity while reducing the subsidisation and, as a consequence, the lifetime artificial rents.